Comparación de métodos de tostado y molido para café robusta a nivel de consumidores en Manabí - Barberán Molina, Miguel Vicente (2025)
The purpose of this study was to characterize the different consumer segments of coffee in the northern zone of Manabí, identifying their preferences, consumption habits, and socioeconomic profiles. The study was conducted in two phases: a survey in the northern cantons of Manabí and a coffee tasting experiment involving regular consumers. In the first phase, surveys were carried out in the cantons of Chone, Bolívar, and Pedernales, with a sample of 172 individuals, excluding 31 respondents who reported not consuming coffee. In the second phase, an experimental design based on Taguchi’s orthogonal principles was used to evaluate the performance of different roasting, grinding, and processing treatments. The factors studied were roast level (medium or dark), grind size (medium or coarse), and production process (artisanal or industrial). The tasting phase applied an experimental design with nine treatments and ten repetitions. Overall, consumers valued flavor, aroma, and freshness, with a tendency to consume coffee mostly in the morning. According to the Taguchi matrix, the optimal combination of parameters—dark roast, coarse grind, and semi-industrial processing—produced the most accepted consumption levels. It was determined that consumers prefer roasted and ground coffee, highlighting flavor intensity as the main attribute when making a purchase.